Targeted inhibition of the methyltransferase SETD8 synergizes with the Wee1 inhibitor adavosertib in restraining glioblastoma growth - Rosa Della Monica; Michela Buonaiuto; Mariella Cuomo; Cristina Pagano; Federica Trio; Davide Costabile; Giulia de Riso; Francesca Sveva Cicala; Maddalena Raia; Raduan Ahmed Franca; Marialaura Del Basso De Caro; Domenico Sorrentino; et al. (Cell Death and Disease, 2023)
Abstract Despite intense research efforts, glioblastoma remains an incurable brain tumor with a dismal median survival time of 15 months. Thus, identifying new therapeutic targets is an urgent need. Here, we show that the lysine methyltransferase SETD8 is overexpressed in 50% of high-grade gliomas. The small molecule SETD8 inhibitor UNC0379, as well as siRNA-mediated inhibition of SETD8, blocked glioblastoma cell proliferation, by inducing DNA damage and activating cell cycle checkpoints. Specifically, in p53-proficient glioblastoma cells, SETD8 inhibition and DNA damage induced p21 accumulation and G1/S arrest whereas, in p53-deficient glioblastoma cells, DNA damage induced by SETD8 inhibition resulted in G2/M arrest mediated by Chk1 activation. Checkpoint abrogation, by the Wee1 kinase inhibitor adavosertib, induced glioblastoma cell lines and primary cells, DNA-damaged by UNC0379, to progress to mitosis where they died by mitotic catastrophe. Finally, UNC0379 and adavosertib synergized in restraining glioblastoma growth in a murine xenograft model, providing a strong rationale to further explore this novel pharmacological approach for adjuvant glioblastoma treatment.